Structural behavior of bolted steel lap shear connections with thermally insulating filler plates. (April 2020) - Mahmood, Salih Qasim; Schumacher, Thomas; Dusicka, Peter; Zareh, Hormoz
Abstract: Non-steel filler plates consisting of thermally insulating materials are used in steel connections to reduce thermal bridging. This research study evaluated the structural behavior of bolted lap shear connections with such materials by means of experimental load testing and finite element (FE) modeling. The main focus of this study is the ultimate strength of the connection, but the slip critical behavior was studied as well to give a more complete understanding of the connection response. Eight specimens having steel and polypropylene (PP) filler plates of various thicknesses were tested in the laboratory and the collected measurements were utilized for numerical validation of a FE model. Subsequently, three parametric studies were conducted using the validated FE models to provide insight into the general behavior of connections with a variety of filler plates that could be used as thermal breaks. In addition, an extreme notional case of filler plates having no strength and stiffness was also considered. This paper presents the experimental program and the FE model, discusses the parametric study evaluating a range of potential filler plate materials, and compares them with existing design code and other equations proposed in the literature. A lower strength reduction factor is recommended for PP as compared to steel filler plates. Highlights: The behavior of bolted steel lap shear connections containing non-steel filler plates is investigated. Non-steel filler plates made of polypropylene (PP) significantly reduce thermal bridging in a connection. Experimental test results are accurately predicted using finite element (FE) modeling. New strength reduction factors for bolted lap shear connections with non-steel filler plates are proposed.